How Much Energy Can Superman Release During a Super Flare? - Uwuigbe, Osarenkhoe (Journal of Interdisciplinary Science Topics, 2017)
This paper investigates how much solar energy Superman can store and subsequently release in the form of his new power, a Super Flare. Modelling Superman’s cells as tiny solar panels it was calculated that 7.07 x 105 J of energy is stored every second by Superman. This figure was adjusted to represent an efficiency which reflected Superman’s abilities; a new value of 3.86 x 1010 J every second was produced. Assuming that Superman can release the energy as fast as he stores it, then Superman releases 3.86 x 1010 J every second during a Super Flare which after an hour would have released more energy than an atomic bomb.